Kobold: web usability as a service - Grigera, Julián (2017)
While Web applications have become pervasive in today’s business, social interaction and information exchange, their usability is often deficient, even being a key factor for a website success. Usability problems repeat across websites, and many of them have been catalogued, but usability evaluation and repair still remains expensive. There are efforts from both the academy and industry to automate usability testing or to provide automatic statistics, but they rarely offer concrete solutions. These solutions appear as guidelines or patterns that developers can follow manually. This paper presents Kobold, a tool that detects usability problems from real user interaction (UI) events and repairs them automatically when possible, at least suggesting concrete solutions. By using the refactoring technique and its associated concept of bad smell, Kobold mines UI events to detect usability smells and applies usability refactorings on the client to correct them. The purpose of Kobold is to deliver usability advice and solutions as a service (SaaS) for developers, allowing them to respond to feedback of the real use of their applications and improve usability incrementally, even when there are no usability experts on the team. Kobold is available at: http://autorefactoring.lifia.info.unlp.edu.ar. A screencast is available at https://youtu.be/c-myYPMUh0Q